2020
DOI: 10.1371/journal.pone.0242003
|View full text |Cite
|
Sign up to set email alerts
|

Shade is the most important factor limiting growth of a woody range expander

Abstract: The expansion of woody plants into grasslands and old fields is often ascribed to fire suppression and heavy grazing, especially by domestic livestock. However, it is also recognized that nutrient availability and interspecific competition with grasses and other woody plants play a role in certain habitats. I examined potential factors causing range- and niche expansion by the eastern redcedar Juniperus virginiana, the most widespread conifer in the eastern United States, in multifactorial experiments in a gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 148 publications
(260 reference statements)
1
15
0
Order By: Relevance
“…Despite this, spraying fungicide impacted seedling height more under high light than low light, indicating that pathogen pressure was higher when light was abundant and that fungal pathogens exerted negative impacts on seedling performance beyond what was visible on leaves. Overall, though, light limitation had the largest influence on seedling performance, overwhelming both nitrogen limitation and pathogen pressure ( Ward, 2020 ). Given this, it appears that the shade-intolerant species L. styraciflua can be excluded from later-successional habitats solely by reducing light availability—high pathogen pressure and nitrogen limitation may further promote this, but are not required.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite this, spraying fungicide impacted seedling height more under high light than low light, indicating that pathogen pressure was higher when light was abundant and that fungal pathogens exerted negative impacts on seedling performance beyond what was visible on leaves. Overall, though, light limitation had the largest influence on seedling performance, overwhelming both nitrogen limitation and pathogen pressure ( Ward, 2020 ). Given this, it appears that the shade-intolerant species L. styraciflua can be excluded from later-successional habitats solely by reducing light availability—high pathogen pressure and nitrogen limitation may further promote this, but are not required.…”
Section: Discussionmentioning
confidence: 99%
“…Third, light limitation may lead to the down-regulation of both the salicylic and jasmonic acid pathways ( De Wit et al, 2013 ), which are key to responding to attack by pathogens and herbivores ( Thaler, Humphrey & Whiteman, 2012 ; De Wit et al, 2013 ; Ballaré & Pierik, 2017 ). Moreover, nutrient limitation may be especially detrimental for shade-intolerant species (e.g., Ward, 2020 ), because it can drastically reduce their ability to build photosynthetic machinery and some defensive compounds ( Coley, Bryant & Chapin, 1985 ; Stamp, 2003 ; Hanssen et al, 2020 ). Thus, susceptibility to pathogens among shade-intolerant species may be particularly high when light and nutrients are limiting ( Kitajima & Poorter, 2010 ; Griffin et al, 2016 ; Griffin et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results have been obtained in other studies that determined the effects of competition by grasses on trees 48-51 . Ward (2020, 2021) 29,54 showed that shade is the most important factor affecting the growth rate and biomass of ERC. On the other hand, we found no evidence of the negative effect of post oak competition on ERC performance, likely due to the niche differentiation between the ERC and post oak.…”
Section: Discussionmentioning
confidence: 99%
“…An important factor that contributes to the improved growing conditions of ERC is reduced plant competition with neighboring plants 28 , such as grasses (Ward, 2020). A major grass competitor is Bromus inermis (hereafter smooth brome).…”
Section: Introductionmentioning
confidence: 99%